2017
DOI: 10.21776/ub.jpacr.2017.006.03.338
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography for Analysis of Metformin in Myrmeleon sp.

Abstract: Myrmeleon sp. is typical of insect larva which has been used in Indonesia for diabetes treatment. However, there is no sufficient scientific report explaining the bioactive compounds in this insect. Based on our preliminary research, this insect contained metformin, i.e. one of bioactive compounds for the treatment of type-2 diabetes. Therefore, this study is focused on the development of separation technique using high-performance liquid chromatography (HPLC) on a reverse phase C-18 column with UV detection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Results of this study showed that M. formicarius (antlion) extract exhibited glucose-lowering effects in streptozotocin-induced diabetic mice. This effect could be attributed to the presence of sulphonylurea- and metformin-like compounds in M. formicarius (antlion) larvae 21, 22, 28, 29. The presence of sulphonylurea compound was verified by the observation of a yellow band on the TLC plate, which is in line with the findings of a previous study 26 .…”
Section: Discussionsupporting
confidence: 87%
“…Results of this study showed that M. formicarius (antlion) extract exhibited glucose-lowering effects in streptozotocin-induced diabetic mice. This effect could be attributed to the presence of sulphonylurea- and metformin-like compounds in M. formicarius (antlion) larvae 21, 22, 28, 29. The presence of sulphonylurea compound was verified by the observation of a yellow band on the TLC plate, which is in line with the findings of a previous study 26 .…”
Section: Discussionsupporting
confidence: 87%
“…Antlion (Myrmeleon sp.) contains chemical compound such as metformin, ALA, and LA that can ameliorate cellular damages caused by either inflammatory process or ROS through various mechanisms (Canetti et al, 2014;Jiang et al, 2017;Muadifah et al, 2017;Malcicka, Visser and Ellers, 2018). Through its anti-inflammatory actions, Metformin was able to protect pancreatic islet damage caused by lowdose multiple injection of Streptozotocine in mice (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation proteins are widely used for MTF analysis, although simple and fast but not specific and less effective in removing other analytical disorders. Pairing ion liquidliquid extraction [7][8][9][10] and solid liquid extraction [11] have also been developed to overcome the polarity of MTF. Ultrafiltration with the cation exchange column has also been reported but its sensitivity is low [12].…”
Section: Introductionmentioning
confidence: 99%